D’infirmière vers professeur des écoles : reconversion professionnelle et identité personnelle - Agnès Guillot; Soazig Lanoë (Recherches en Éducation)
A quarter of the nurses suffer from professional exhaustion. Resigning and conversion in this professional area, if frequent, are not much observed. A monographic study, analyzing the career of a nurse who became primary school teacher, allowed us to understand the dynamic of her professional change, and the recomposition of her professional identity, grounded in highly personal values. A destabilisation of her self-skill feeling was determining in her decision to engage in a deliberate professional change, her self-esteem being challenged by professional wearing down and by the confrontation to her patients' death. She has been able for reconstruct both her self-esteem and skill feeling, and to reveal nursing skills reinvested as a teacher. Supported by her original institution, and by a “significant other”, she prepared her profession change project and engaged in it, faithful to her identifications and to herself. This study is predicated on an ascending approach and a reciprocal analysis of different corpus, including clinical interviews and questionnaires analyzing the careers. It is based on the first professional occupation and its pressures, the decision–making process about the reconversion as a teacher and its conditions, as well as the different phases of the deliberate professional change.